2016
DOI: 10.1371/journal.pone.0158273
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of BMP2 and Their Association with the Risk of Non-Syndromic Tooth Agenesis

Abstract: Non-syndromic tooth agenesis (or non-syndromic congenitally missing tooth) is one of the most common congenital defects in humans affecting the craniofacial function and appearance. Single nucleotide polymorphisms (SNPs) have been associated with an individual’s susceptibility to these anomalies. The aim of the present study was therefore to investigate the roles of the potentially functional SNPs of BMP2 in the occurrence of tooth agenesis. Overall, four potentially functional SNPs of BMP2 (rs15705, rs235768,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…More than 60 syndromes catalogued in Online Mendelian Inheritance in Man (OMIM) are associated with agenesis. Non-syndromic tooth agenesis involves a congenitally missing tooth in an isolated form, without an association with any other major birth defects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 60 syndromes catalogued in Online Mendelian Inheritance in Man (OMIM) are associated with agenesis. Non-syndromic tooth agenesis involves a congenitally missing tooth in an isolated form, without an association with any other major birth defects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, much progress has been made in the identification of the developmental basis of odontogenesis and the genes involved in TA. [6][7][8][9][10][11][12] In fact, genetic polymorphisms in many genes, including MSX1 (msh homeobox 1), 20 PAX9 (paired box 9), 20 FGF3 (fibroblast growth factor 3), 7 FGF10 (fibroblast growth factor 10), 7 FGFR2 (fibroblast growth factor receptor 2), 7 FGFR1 (fibroblast growth factor receptor 1), 21 BMP2 (bone morphogenetic protein 2), 6 BMP4 (bone morphogenetic protein 4), 10,12 TGF 1 (transforming growth factor beta 1), 11 TGF 3 (transforming growth factor beta 3), 10 IRF6 (interferon regulatory factor 6), 9 MMP1 (matrix metalloproteinase 1), 22 MMP20 (matrix metalloproteinase 20), 22 MMP9 (matrix metalloproteinase 9), 10 MMP13 (matrix metalloproteinase 13), 10 and AXIN2 (axin-related protein 2) 20 have been associated with non-syndromic TA. However, to the best of our knowledge, this is the first study evaluating genetic ESR2 and tooth agenesis Marañón-Vásquez et al…”
Section: Discussionmentioning
confidence: 99%
“…Non-syndromic TA includes a congenitally missing tooth (or teeth) in an isolated form, without an association with any other major birth defect. 6 However, several studies have proposed a strong genetic background for isolated TA. [6][7][8][9][10][11][12] Estrogen regulates cell growth, differentiation, and development.…”
Section: Introductionmentioning
confidence: 99%
“…Phan et al investigated the previous literature and finally identified nine genomic loci and 26 candidate genes leading to the co‐occurrence of these two congenital defects (Phan et al, ). In addition, BMP2 , BMP4 , and WNT signaling‐related genes (i.e., WNT10A , WNT3 , AXIN2 ) had also been found in association with TA and NSCL/P (Gong et al, ; Lu et al, ; Song et al, ).…”
Section: Introductionmentioning
confidence: 99%